The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5901/mjss.2017.v8n1p330
|View full text |Cite
|
Sign up to set email alerts
|

News Media Exposure and Political Communication among Libyan Elites at the Time of War

Abstract: Many critical questions concerning the relationship between the news media and political knowledge involve the extent to which the media facilitate learning about news, war and politics. Political awareness -via the news media -affects virtually every aspect of citizens' political attitudes and behaviours. This paper examines how

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The result indicated that the news coverage of Egypt was not balanced and that this had been the case since 2011, as Hroub (2011) argues. This is unsurprising as Al-Jazeera is already known for its support of some ideological and political views in the Arab world (Lynch, 2015) which reflect its interests and agenda (Ziani, Elareshi, & Al-Jaber, 2017), concerning events in Syria, Egypt and Libya, but not in Bahrain (Mejalli, 2019). An open-ended question asked the participants to indicate/highlight three keywords/phrases that they could use to describe the online information delivered about Egypt (Figure 1).…”
Section: Findings a Survey Results News Contentmentioning
confidence: 99%
“…The result indicated that the news coverage of Egypt was not balanced and that this had been the case since 2011, as Hroub (2011) argues. This is unsurprising as Al-Jazeera is already known for its support of some ideological and political views in the Arab world (Lynch, 2015) which reflect its interests and agenda (Ziani, Elareshi, & Al-Jaber, 2017), concerning events in Syria, Egypt and Libya, but not in Bahrain (Mejalli, 2019). An open-ended question asked the participants to indicate/highlight three keywords/phrases that they could use to describe the online information delivered about Egypt (Figure 1).…”
Section: Findings a Survey Results News Contentmentioning
confidence: 99%
“…In this context, there is a ubiquity of SNSs in war and conflict zones where technology is transforming how we receive and participate in news and information. There is no doubt that the media have had great effects, especially during wartime and conflicts in the Arab world, such as the recent so-called Arab Spring of 2011 and the wars in Iraq since the early 1980s, where the influence of various media has increased via the adoption of satellite TV services (Al-Asfar, 2002;Ayish, 2002) and then the Internet (Ward et al, 2008;Ziani et al, 2017) and SNSs (Ghanem, 2012;Rauniar et al, 2014;Singer, 2015).…”
Section: Introductionmentioning
confidence: 99%